Indonesian – English Code Mixing Used in Hello Cello Novel - Citra Dewi, Ni Putu; Tustiawati, Ida Ayu Mela (English Language and Literature, 2024)
This study aims to analyze the types and reasons of code mixing used in Hello Cello Novel by Nadia Ristivani. To achieve these goals, this study used a descriptive qualitative method and theory by Hoffman (1991). The data was taken from Hello Cello Novel by Nadia Ristivani. The result of this study shows 110 total data of code mixing in this study. There are three types of code mixing found, namely 95 data or 86% of intra sentential which made it as the most dominant types found in the study, 14 data or 13% of intra lexical, and 1 data or 1% involving a change of pronunciation. Meanwhile for the reasons of code mixing it was found seven reasons that why the character use code mixing in the novel. Those are; 85 data or 77% to talk about a particular topic which was the dominant finding in this study, 1 data or 1% to quote somebody else, 12 data or 11% to show empathy about something, 5 data or 5% due to interjection, 3 data or 3% to show repetition used for clarification, 2 data or 1,5% on intention of clarify the speech content for interlocutor and 2 data or 1,5% to express group identity.Key words: Code, Code Mixing, Hello Cello Novel